DINAMIKA PENGELOLAAN ZAKAT DI KANTOR KEMENTERIAN AGAMA KABUPATEN DEMAK - Salma Munawwaroh; Nura Fajria (Asketik : Jurnal Agama dan Perubahan Sosial, 2021)
Indonesia as a country with the largest number of Muslims has tremendous potential in alleviating poverty, namely through zakat, but this potential has not been realized in achieving this goal. The Ministry of Religion as an institution that has the main task and function as zakat management should have best practice in zakat management. This study aims to identify the management of zakat in the Office of the Ministry of Religion of Demak Regency. The results of this study reveal that zakat in the Ministry of Religion of Demak Regency is not optimal for Amil or zakat managers because the management is not arranged ex-officio. Management still uses the old way, which is just distributing zakat without thinking about contemporary zakat management. The management of zakat at the Office of the Ministry of Religion of Demak Regency does not have supervision and transparency for muzakki. The researcher's recommendation is that ex-officio restructuring of amil is needed, and it is necessary to form a discussion group forum as an effort to equip amil's understanding of contemporary zakat management. And a monitoring system is needed for the management of zakat and the need for data transparency so that Muzakki's trust in Amil is createdIndonesia as a country with the largest number of Muslims has tremendous potential in alleviating poverty, namely through zakat, but this potential has not been realized in achieving this goal. The Ministry of Religion as an institution that has the main task and function as zakat management should have best practice in zakat management. This study aims to identify the management of zakat in the Office of the Ministry of Religion of Demak Regency. The results of this study reveal that zakat in the Ministry of Religion of Demak Regency is not optimal for Amil or zakat managers because the management is not arranged ex-officio. Management still uses the old way, which is justdistributing zakat without thinking about contemporary zakat management. The management of zakat at the Office of the Ministry of Religion of Demak Regency does not have supervision and transparency for muzakki. The researcher's recommendation is that ex-officio restructuring of amil is needed, and it is necessary to form a discussion group forum as an effort to equip amil's understanding of contemporary zakat management. And a monitoring system is needed for the management of zakat and the need for data transparency so that Muzakki's trust in Amil is createdKeyword: Management, Zakat, Ministry of Religious Affairs